A new SERS substrate based on niobium lead-pyrophosphate glasses obtained by Ag+/Na+ ion exchange - Manzani, Danilo; Franco, Douglas F. [UNESP]; Afonso, Conrado R.M.; Sant'Ana, Antônio C.; Nalin, Marcelo [UNESP]; Ribeiro, Sidney J.L. [UNESP] (Elsevier, 2018)
Surface-enhanced Raman scattering (SERS) is one of the most sensitive methods for the detection of adsorbed molecules on the nanostructured coinage-metal surface. The enhancements in the order of 104–106 are routinely observed. Such an effect makes SERS spectroscopy a technique applicable to the study the adsorption of analytes in the submonolayer regime. Novel SERS sensors require novel substrates with high activity for great sensibility detection of different molecules applied in many fields, such as detections of narcotics, explosives, and molecules with biological interest. In this work, silver nanoparticles embedded in niobium lead-pyrophosphate glasses (Pb2P2O7-Nb2O5-Na2O) were prepared by ion exchange process, where silver ions were introduced into glass surface by Ag+/Na+ ion exchange (NaNO3:AgNO3 batch), and reduced to metallic silver by heat treatment at glass transition temperature (ca. 480 °C). The new substrate was characterized by Raman spectroscopy, optical absorption, transmission electron microscopy (TEM) and atomic force microscopy (AFM). Its application in SERS was demonstrated by studying the adsorption of 2,2-bipyridine (bpy) on the glass surface, which has marker bands for the coordination of the adsorbate with silver atoms. The optimal surface features in terms of SERS enhancement were also discussed and the sensing ability of this new substrate was demonstrated.
Keywords: Ion exchange; Phosphate glass; Raman spectroscopy; SERS; Trace analysis